An Azerbaijani Adaptation of the Lifespan Sibling Relationship Scale: Investigating Its Impact on Life Satisfaction and Psychological Resilience - Aliyev, Bakhtiyar; Zalova Nuriyeva, Ulkar; Rustamov, Elnur; Nasibova, Emilya; Yusifova, Tamara; Abbasova, Sevil (Technium Social Sciences Journal, 2025)
The main purpose of this study is to adapt the Lifespan Sibling Relationship Scale for use in the Azerbaijani context and explore its association with psychological resilience and satisfaction with life. Data were gathered through a convenience sampling method, including a total of 367 individuals, aged 18 to 59 years (M=25.04, SD=7.60). The adaptation process of the Lifespan Sibling Relationship Scale involved Confirmatory Factor Analysis (CFA), Item Response Theory (IRT), and assessments of convergent validity and reliability (including Cronbach's α, McDonald's ω, and Guttmann's λ6). Furthermore, CFA supported the six dimensional structure of LSRS, despide one item of scale indicating factor loading above 0.30 and could not be taken into account in Azerbaijani context. IRT analysis was also conducted and results demonstrated that all items have excellent fit with the model. Additionally, results obtained from reliability analysis demonstrated that the Azerbaijani version of the LSRS presented sufficient reliability coefficient. Relationships between sibling relationships, life satisfaction and psychological resilience were investigated as well and the LSRS was found to be correlated with life satisfaction and psychological resilience. In summary, results of adaptation of Sibling Relationship Scale into Azerbaijani demonstrated excellent psychometric propertiess.